Kayak Drone – a silent acoustic unmanned surface vehicle for marine research - Totland, Atle; Johnsen, Espen (Frontiers in Marine Science, 2022)
Advancements in technologies have led to a rapid development of unmanned surface vehicles (USV) for marine ecosystem monitoring. The design, size, and scientific payload of the USVs differ as they are built for different purposes. Here, we present the design criteria and detailed technical solutions of a prototype USV which has been built to fulfill the following experimental and operational needs; the USV should be used for inshore and shallow water acoustic monitoring, offshore comparison of echo sounder recordings from the USV and research vessels, monitor natural fish schooling behavior and seabird-fish behavioral interactions. The prototype has been built over a period of 5 years with steadily quality improvements. As the hull is based on an expedition double kayak, the USV is named Kayak Drone, and we aimed at building the Kayak Drone using of-the-shelf hardware and existing open-source software. This allowed for the development of a modular and well-functioning USV at a relatively low cost. The Kayak Drone produces very little noise and in situ experiments show that the Kayak Drone can record echo sounder data of fish near the surface without disturbing their natural distribution and behavior. One in situ study shows that the Kayak Drone could navigate within a couple of meters from swimming puffin and other seabirds without triggering escape. These results demonstrate that the Kayak Drone can be utilized to produce unbiased survey estimates for fish distributed in shallow waters and near the surface, which is very important for many fish stock assessments and managements. Furthermore, it can also be used as a tool to observe the predation by seabirds on fish schools without interfering with their natural interspecific behavior, which traditionally has been very difficult. The use of the Kayak Drone is not restricted to these tasks, and we foresee that the Kayak Drone can be utilized in many different experiments where a silent platform is needed.